Gendered Negotiations: Engagements with ‘Modernity’ and Identity Change amongst Chiapeneco Youth in Mexico - Ruse, Jamie-Leigh (Studies of Transition States and Societies, 2011)
In this paper I wish to examine how changes have occurred in the processes of gendered identity construction amongst Mexican youths through examining local experiences of global, and speciﬁ cally Mexican, modernities. Based on ﬁ eldwork carried out amongst youths in the city of San Cristobal de las Casas, in the southern Mexican state of Chiapas, my analysis addresses how youths plan for the future in the context of economic and political marginalisation, and how this aﬀ ects the way in which they pursue diﬀ erent forms of romantic relationships. I also address changes that have occurred in youths’ understandings, perceptions and performances of their gendered identities in the context of a highly developed local tourist industry, the advent of mass media, and new online social worlds. My study shows how gendered identity construction amongst youths here becomes context-dependent, and how it encompasses individual agency whilst at the same time being negotiated through wider structural and social limitations. I also wish to demonstrate how changing gendered identities amongst youths are constantly constructed and renegotiated by individuals seeking to accommodate notions of modernity with perceptions of the traditional, and how these individuals balance contesting notions of gendered identities within themselves. This is, therefore, a study of local and gendered identity change amongst youths in the context of localised modernities and rapid social change.